Variation in isolates of Sclerotinia sclerotiorum (Lib.) de Bary causing white mold disease in Bangladesh crops. (October 2019) - Nahar, M.S.; Naher, Najmun; Alam, M.J.; Hossain, M.S.; Mian, M.Y.; Miller, S.A.
Abstract: Ten isolates of Sclerotinia sclerotiorum, namely country bean ( Lablab purpureus L.), Bogra; country bean ( Lablab purpureus L.), Hobigonj; eggplant ( Solanum melongena L.), Pabna; sunflower ( Helianthus annuus L.), Pabna; mustard ( Brassica rapa L.), Pabna; mustard ( Brassica rapa L.), Bogura; mustard ( Brassica rapa L.), Joypurhat; marigold ( Tagetes erecta L.), Gazipur; Sylvia ( Salvia colorans Bemth), Gazipur and weed ( Sida rhombifolia L.), Bogra were collected from Bogra, Hobigonj, Pabna, Joypurhat and Gazipur district of Bangladesh. Among them seven isolates were tested for production of oxalic acid in culture media and pathogenicity by inoculating on country bean, eggplant, marigold leaves. All the isolates of S. sclerotiorum produced oxalic acid in bromophenol blue amended potato dextrose agar (PDA) media and PD broth, and evidence of oxalic acid production was confirmed as changing of media color. Radial growth of mycelium was higher in isolates of mustard and eggplant from Pabna, marigold from Gazipur, country bean from Bogra and Hobigonj. Deep bright yellow color with higher luminosity values (35.58–36.84) was recorded in the isolates of mustard and eggplant from Pabna. Higher pH reduction (42.8%–50.6%) with changing of color from blue to yellow was recorded in the isolates of country bean in Bogra and, mustard and sunflower in Pabna. Oxalic acid production was higher in the isolates of mustard, Pabna (23.55 mM) and weed, Bogra (21.54 mM). Isolates of country bean, Bogra and eggplant, Ishordi produced 14.67 mM and 13.40 mM oxalic acid, respectively. The lowest oxalic acid (8.74 mM) was produced in the isolate of marigold, Gazipur. Isolates of country bean in Hobigonj and Bogra, weed in Bogra and eggplant in Pabna developed symptoms size 4.62–7.78 cm on country bean leaves. Severe infection and rapidly developing symptoms (5.00–9.00 cm) were observed on eggplant leaves when the isolates of country bean in Hobigonj and Bogra, marigold in Gazipur, sunflower and eggplant in Pabna were inoculated. All seven isolates infected and produced symptoms on marigold leaves; however the size of symptoms varied. While ten isolates were examined for melanin synthesis in PDA media, all isolates produced melanin except the ones collected from Pabna regardless of crops. Isolates differed significantly for mycelial growth, media luminosity and pathogenicity. A positive correlation was found between mycelial growth and luminosity values, between mycelial dry weight and media pH and oxalic acid productions. Isolates also varied in relation to the time required to produce visible symptoms on the host plants. Highlights: Different isolates of Sclerotinia sclerotioum were studied. Positive correlation was observed between mycelial growth and oxalic acid production. Variation was found among the isolates of S. sclerotiorum for oxalic acid production, melanin synthesis and pathogenicity.